Legal Reform Post-Demonstration: An Analysis of the Impact of Protests on Public Policy - Sutawijaya, Darmawan (PT. Anagata Sembagi Education, 2025)
Demonstrations represent a crucial democratic mechanism for expressing public aspirations regarding state policies. The August 25, 2025 protests in Indonesia illustrate how socio-political pressure can drive legal reform and influence public policy, particularly concerning the transparency and accountability of legislative institutions. This study aims to analyze the impact of public demonstrations on the dynamics of legal reform and their effects on public policy. Based on this background, the research questions are: first, how do demonstrations affect legal reform in Indonesia; and second, to what extent do protests influence public policy changes, especially in terms of legislative transparency and accountability. The research employs a normative-juridical approach complemented by a socio-legal perspective, with a descriptive-analytical design. Primary data consists of legislation and regulations, secondary data from literature and media reports, and tertiary data from legal dictionaries and supporting documents. Data were collected through library research, media documentation, and document analysis, and were analyzed qualitatively. The findings indicate that the August 25, 2025 protests acted as a catalyst for legal reform and prompted shifts in public policy towards good governance principles, enhancing transparency, accountability, and public participation in the legislative process.